Including learners with low-incidence disabilities - West, Elizabeth A., 1968- (Bingley, U.K. : Emerald, 2015)
This Volume focuses on inclusive education for the less than 1 of school-age population who have been diagnosed with Low-Incidence Disabilities and continue to be marginalized in many ways. This unique contribution provides a wide-range of perspectives on what works to facilitate inclusion in a variety of contexts. In many countries teachers are being asked to ensure that all of their students achieve, regardless of background or disability leaving many grappling with how to facilitate inclusion for learners with low-incidence disabilities. The first section of this text presents strategies and supports for inclusion. It offers the reader examples of good practices that practitioners can employ to improve teaching and learning in their school or classroom for these students and their families. The second section offers a range of international perspectives that illuminate the work being done related to inclusion for learners with low-incidence disabilities within those contexts. This important book highlights the need to include learners with low-incidence disabilities and provides information related to supports and services to achieve that goal across a variety of contexts.
Moving towards inclusion / Elizabeth A. West -- Beyond access : moving towards increased participation, membership, and skills in the inclusive classroom / Grace I. Blum, Michael Gutierrez, Charles Peck -- Best practices in teacher training and professional development for including learners with low-incidence disabilities / Meaghan M. McCollow, Jordan Shurr, Andrea D. Jasper -- Including learners with severe intellectual disabilities : system planning and support for greater inclusive practices / Vicki Barnitt, Phyllis Jones, Daphne Thomas -- Facilitating systems of support / Robin Drogan, Darlene Perner -- Facilitating supports and services for learners with low-incidence disabilities / Jody Marie Bartz, Jennifer Kurth, Matthew Wangeman -- Providing appropriate individualized instruction and access to the general education curriculum for learners with low-incidence disabilities / Jeremy Erickson, Carol Ann Davis -- Socio-emotional support needs for re-entry to school after traumatic brain injury / Anne E. Crylen -- This is what works for me : students reflect on their experiences of special needs provision in Irish mainstream schools / Richard Rose, Michael Shevlin -- Inclusive education for students with low-incidence disabilities in Taiwan : where we are, what we have learned / Pei-Yu Chen, Chun-Yu Chiu -- Low incidence learners in Sweden : supporting systems and social interactions in education / Daniel Östlund -- Inclusive education for learners with severe, profound and multiple learning difficulties in England / Penny Lacey, Jeanette Scull -- 21st century inclusive practices and policies in Russia / Vita L. Jones ... [et al.] -- Including learners with extensive support needs in South Korea / Kyungsook Kang, Young Hyuk Hong -- Inclusive education in Poland : policies, practices and perspectives / Kinga M. Ober, Andrzej Twardowski, Melinda R. Pierson.
Includes index.
Print version record
Keywords: Education -- Inclusive Education; Education -- General; Education -- Administration -- General; Inclusive education / mainstreaming; Schools; Inclusive education